CHEMICAL COMPOSITION OF MAIN BRAZILIAN WINTER CEREALS - GUARIENTI, ELIANA MARIA (2001)
Com is the main cereal used in Brazil for pigs and poultry feeding. Its price variation in the last years has led to contemplate the use of other alternatives to its substitution. There is little information in Brazil regarding technical and economic viability of winter cereais use as an alternative feeding for animais. Therefore, knowledge of the chemical composition is of paramount importance in the feeding.formulation for different animal.species. This study aimed to verify the chemical composition of the grains of the main winter cereais produced in the country (white oats, black oats, rye, barley, triticale and wheat). Winter cereal grain samples of a field trial planted in Embrapa Trigo, Passo Fundo, RS, under a randomized block design with three replications were analysed in Embrapa Suínos e Aves, Concórdia, SC, relatively to dry matter, crude.protein, fat, crude fibre, ash, non-nitrogenous substancesand crude energy. The results obtained with the different w inter cereais were advantageous comparatively to corn in animal feeding formulation, suggesting that they show potentiality to be used as a viable alternative.